Blood Glucose Level, Blood Pressure, and Medication Behavior are related to Cardiovascular Complication in Hypertension Patient at Sikumana Public Health Center (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2020)
Hypertension tends to be incurable and can only be controlled, including to prevent cardiovascular complications. The purpose of this study was to look at the relationship of age, gender, blood glucose level, blood cholesterol level, blood pressure, and medication behavior (consumption of drugs and health control) with the incidence of cardiovascular complications in patients with hypertension at the Public Health Center in Sikumana-Kupang City. This study used a cross sectional design with a sample of 87 hypertension patients. Data analysis used Rank Spearman's Test (Î± = 0.01). There were 50 respondents who had cardiovascular complications in the form of non- hemorrhagic stroke complications (NHS), complications of coronary artery deseases (CAD), NHS and CAD complications, and complications of anggina pectoris. Analysis of Rank Spearman indicated age had p = 0.404 and r = 0.091, gender had p = 0.161 and r = -0,152, blood glucose level had p = 0.000 and r = -0.390, blood cholesterol level had p = 0.272 and r = -0.119, blood pressure had p = 0.000 and r = +0.417, drug consumption had p = 0.000 and r = +0.439, and health control had p = 0.000 and r = +0.490. It was concluded that there were significant relationships between blood glucose levels, blood pressure, and medication behavior (which consists of the consumption of hypertension drugs and health control) with the incidence of cardiovascular complications in patients with hypertension at the Sikumana Public Health Center in Kupang City.